Medicaid Accountable Care Organizations and Childbirth Outcomes. (December 2020) - Henke, Rachel Mosher; Karaca, Zeynal; Gibson, Teresa B.; Cutler, Eli; White, Chapin; Head, Michael; Wong, Herb S.
Some states have adopted Accountable Care Organization (ACO) models to transform their Medicaid programs, but little is known about their impact on health care outcomes and costs. Medicaid ACOs are uniquely positioned to improve childbirth outcomes because of the number of births covered by Medicaid. Using Healthcare Cost and Utilization Project hospital data, we examined the relationship between ACO adoption and (a) neonatal and maternal outcomes, and (b) cost per birth. We compared outcomes in states that have adopted ACO models in their Medicaid programs with adjacent states without ACO models. Implementation of Medicaid ACOs was associated with a moderate reduction in hospital costs per birth and decreased cesarean section rates. Results varied by state. We found no association between Medicaid ACOs and several birth outcomes, including infant inpatient mortality, low birthweight, neonatal intensive care unit utilization, and severe maternal morbidity. Improving these outcomes may require more time or targeted interventions.